Comparative Evaluation of Color Stability of Maxillofacial Silicones Following Accelerated Aging Conditions. Issue 2 (June 2022) - Nair, Abha; Saratchandran, Sudeep
Objectives: This study evaluated & compared the effect of both outdoor weathering and accelerated aging conditions on the color stability of two different maxillofacial silicone elastomers. Methods: 72 samples of two different silicones were made and divided into groups of conditioning; Dark storage, accelerated aging and outdoor weathering. Color measurements were recorded by Commission Internationale de l'Eclairage–CIE L*a*b* color system before and after conditioning using spectrophotometer. The data was analyzed by one way ANOVA for multiple Group comparisons, followed by Post hoc Scheffe's Multiple comparison test for Group wise calculation at the 0.05 significance level. Results: All groups exhibited variation in color over time. The color change (∆E) of the pigmented specimens of all tested High Temperature Vulcanization—HTV & Room Temperature Vulcanization—RTV silicone elastomers were greater than the acceptable value (∆E >3.0). Within non pigmented HTV specimens, none of the tested silicone elastomers showed signiﬁcant color changes. Within non pigmented RTV specimens, all of the tested silicone elastomers showed signiﬁcant color changes ( P  < .05). The HTV M511 elastomer showed better color stability compared with the RTV A-2186 material. Furthermore, accelerated aging condition was more detrimental and showed significant deterioration of the color properties of both HTV & RTV specimens. Significance: The results of this research will help in providing patients with maxillofacial defects in India, a prosthetic appliance that restores pleasant facial appearance with good esthetics. This will reduce trauma from head & neck cancer surgery & will help people lead a normal life in society.